Sosialisasi Pemanfaatan Layanan G-Suite For Edu (Google Suite for Education) pada SMP Negeri 69 Jakarta: indonesia - Aryani, Diah; Siolemba Patiro, Shine Pintor; Ariessanti, Hani Dewi (Universal Raharja Community (URNITY Journal), 2021)
Education in the current digitalization era requires the ability to adapt to developments in the field of information and communication technology that affect the education system in the digital era. This community service activity aims to take advantage of opportunities by sharing knowledge and increasing knowledge by utilizing information and communication technology by introducing G-Suite for Education as a learning model strategy in the current era of digitalization, especially for teachers of SMP Negeri 69. The method used is the socialization method. practically by providing training and simulating G-Suite for Educations services so that it is hoped that through this socialization it can be achieved understanding and mastery of teachers to be able to use the G-Suite for Education service which consists of Gmail, Calssroom, Docs, Drive and Google Calendar in good learning activities. face-to-face and online. Kata kunci : G-Suite for Education, digitalization era, sharing knowledge